Pertumbuhan Pasca-trauma pada Remaja yang Kehilangan Orang Tua karena Covid-19 - Nita Indriani; Dian Kartika Amelia Arbi (Airlangga University Press, Universitas Airlangga, 2022)
This study aimed to investigate posttraumatic growth (PTG) as a process and outcomes among adolescents facing trauma after losing parents due to Covid-19. This qualitative study used an instrumental case study approach involving three participants. Data were collected using the Posttraumatic Growth Inventory (PTGI) and through interviews with general guidelines. Data were processed using theory-driven thematic analysis and their credibility was ensured through triangulation. The results found that adolescents experience a process of PTG that involved cognitive, emotional, and social components leading to perceived positive changes which could be classified into five dimensions of PTG. This finding explained PTG among adolescents more comprehensively, as it portrayed PTG as a holistic unit, integrating both the process and the outcomes.